Sugarcane Leaf Litter as Soil Amendment to Stimulate Collembolan Diversity - Bambang Tri Rahardjo; Rina Rachmawati; David Soetjipto (AGRIVITA, Journal of Agricultural Science, 2019)
The sugarcane leaf litter contains organic material and if it is returned to the soil, it will increase the diversity of Collembola. Collembola has an important role as a decomposer of soil organic matter and bioindicator of soil health. This study was conducted to determine the effect of sugarcane leaf litter on the diversity of Collembolan in sugarcane plantation at Kebonagung Sugar Factory, Malang. This study was conducted from March to June 2018. Transect method was used in sampling method. The pitfall traps were used to obtain Collembolan samples on the surface of the ground while the Berlese-Tullgren funnels were used to obtain Collembolan samples inside the soil. A total of 5,535 collembolan were collected. Five species were collected, including Brachystomella sp., Folsomides sp., Mesaphorura sp., Alloscopus sp., and Dicranocentrus sp. Applying sugarcane leaf litter to the soil has a positive effect on Collembolan diversity, as evidenced by the increasing value of diversity index on the soil surface from 0.53 to 1.11 and decreasing the value of dominance index on the soil surface from 0.76 to 0.43.